2021
DOI: 10.1002/ddr.21836
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic degradation patterns of the receptor for advanced glycation end products peptide fragments correlate with their neuroprotective activity in Alzheimer's disease models

Abstract: The receptor for advanced glycation end products (RAGE) plays an essential role in Alzheimer's disease (AD). We previously demonstrated that a fragment (60–76) of RAGE improved the memory of olfactory bulbectomized (OBX) and Tg 5 × FAD mice – animal models of AD. The peptide analog (60–76) with protected N‐ and C‐terminal groups was more active than the free peptide in Tg 5 × FAD mice. This study investigated proteolytic cleavage of the RAGE fragment (60–76) and its C‐ and N‐terminally modified analog by blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…1−4 Increasing evidence indicates that MGO, containing two reactive carbonyl groups, is the leading cause (20 000 times more reactive than glucose) for the formation of advanced glycation end products (AGEs) by binding to and modifying arginine, lysine, and cysteine residues in organisms. 5,6 Over the last few decades, AGEs and MGO have received increasingly more attention and been recognized as pathogenetic mediators in chronic diseases, including diabetes, 7 diabetic complications, 8,9 cardiovascular disease, 10 Alzheimer's disease, 11 and so on. Multiple therapeutic options are available to trap MGO or prevent the formation and accumulation of AGEs or alleviate MGO/AGE-induced chronic diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−4 Increasing evidence indicates that MGO, containing two reactive carbonyl groups, is the leading cause (20 000 times more reactive than glucose) for the formation of advanced glycation end products (AGEs) by binding to and modifying arginine, lysine, and cysteine residues in organisms. 5,6 Over the last few decades, AGEs and MGO have received increasingly more attention and been recognized as pathogenetic mediators in chronic diseases, including diabetes, 7 diabetic complications, 8,9 cardiovascular disease, 10 Alzheimer's disease, 11 and so on. Multiple therapeutic options are available to trap MGO or prevent the formation and accumulation of AGEs or alleviate MGO/AGE-induced chronic diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Methylglyoxal (MGO) is primarily generated endogenously as a by-product from glycolysis by the nonenzymatic degradation of triose phosphates, such as glyceraldehyde 3-phosphate and dihydroxyacetone-phosphate and exogenously due to autoxidation of sugar, the Maillard reaction, degradation of lipids, and fermentation during food and drink processing. Formation of MGO accounts for only 0.1% of glucotriose flux with a rate of about 125 μmol/kg cell mass per day under physiological conditions. Increasing evidence indicates that MGO, containing two reactive carbonyl groups, is the leading cause (20 000 times more reactive than glucose) for the formation of advanced glycation end products (AGEs) by binding to and modifying arginine, lysine, and cysteine residues in organisms. , Over the last few decades, AGEs and MGO have received increasingly more attention and been recognized as pathogenetic mediators in chronic diseases, including diabetes, diabetic complications, , cardiovascular disease, Alzheimer’s disease, and so on. Multiple therapeutic options are available to trap MGO or prevent the formation and accumulation of AGEs or alleviate MGO/AGE-induced chronic diseases .…”
Section: Introductionmentioning
confidence: 99%
“…7). However, only peptides P1 and P7 that previously demonstrated the protective activity in vivo [15,16,18] were able to induce ROS production. It was also shown that fragments of the V‐domain of RAGE protect neurons against Aβ induced apoptosis [17] and necrosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE fragments (Table 1) were derived from the sequences of human RAGE (Q15109 UniProtKB/Swis-sProt). The RAGE peptides were synthesized by solid phase method as described previously [15,18].…”
Section: Synthetic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation